ChemInform Abstract: Biocatalysis Applied to the Synthesis of Valuable Triazole‐Containing Derivatives. Issue 4 (January 2015) - Cuetos, Anibal; Bisogno, Fabricio R.; Lavandera, Ivan
Abstract Review: 147 refs.